Molt patterns and age and sex determination criteria for selected landbirds in an urban area of the Peruvian Central Coast - Alexis Díaz; Pamela Ayala; Elizabeth Valdiviezo; Jorge Mendoza; Kathia Silva; Rolf Rivas; Dayanne Cornelio; Fabiola Guardia; Yaquelin Tenorio; Rocío Calsina; Lorena Alvariño; José Iannacone (Caldasia)
Despite molting is an important and expensive activity in the life cycle of birds, this process is poorly known for neotropical species and even less so for species inhabiting urban zones. We studied molt patterns, aging and sexing criteria, and morphometrics for seven common resident species in an urban area of Lima city, Peru. All species evidenced complete prebasic molts. Partial to eccentric incomplete preformative molts were evidenced for six species (Camptostoma obsoletum, Pyrocephalus rubinus, Catamenia analis, Poospiza hispaniolensis, Coereba flaveola, and Thraupis episcopus); whereas Co-lumbina cruziana exhibited a complete molt. All thraupid species exhibited partial prealternate molts. Preformative and prebasic molts were recorded mostly during the dry season, and the few records of prealternate molts might suggest its occurrence soon after the wet season. Our species also exhibited low molt synchrony, with some of them (C. cruziana, P. rubinus, and C. flaveola) exhibiting extensive molt periods likely explained by its potential to reproduce throughout the year and/or the existence of suspended/ protracted molts. Morphometric analysis evidenced significant differences according to sex for C. cruziana, P. rubinus, and C. analis, with the wing chord being the most common characteristic for distinguishing between sexes. Our study covers an important gap in the knowledge of the natural history of urban birds and provides information to test hypotheses of molt pattern variation on species with widespread distribution throughout the Americas.